2016
DOI: 10.1590/0102-33062016abb0250
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene paleoenvironments of the floodplain of the Solimões River, Central Amazonia, based on the palynological record of Lake Cabaliana

Abstract: Th e core PD-67 of 160 cm depth was collected from the delta of Lake Cabaliana situated on the Solimões River. Seventeen samples were removed for palynological and sedimentological analysis and three for radiocarbon analysis. Two dry periods, both in the Late Holocene, were observed (2800-2550 cal yr BP, 1450-550 cal yr BP) separated by a wetter phase (2550-1450 cal yr BP). In 2800-2550 cal yr BP, varzea forests of Alchornea, Symmeria, Cecropia, Alternanthera and Asteraceae were predominant. Beginning in 2,550… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Throughout core 105-AM, spore counts were quite high (Figure 10C), which was similar to other palynological analysis in the Solimões Formation (e.g., Silva-Caminha et al, 2010;Kern et al, 2020). This abundance contrasted with much less fern spores in the Holocene localities compared herein (Absy, 1979;Behling et al, 1999) and elsewhere in Amazonia (e.g., Irion et al, 2006;Sá et al, 2016;Rodríguez-Zorro et al, 2018). However, a pollen study in western Amazonia near the 105-AM site by Roucoux et al (2013) found high fern spore abundances during the formation of a peat deposit in the Late Holocene.…”
Section: Fern Sporessupporting
confidence: 84%
See 1 more Smart Citation
“…Throughout core 105-AM, spore counts were quite high (Figure 10C), which was similar to other palynological analysis in the Solimões Formation (e.g., Silva-Caminha et al, 2010;Kern et al, 2020). This abundance contrasted with much less fern spores in the Holocene localities compared herein (Absy, 1979;Behling et al, 1999) and elsewhere in Amazonia (e.g., Irion et al, 2006;Sá et al, 2016;Rodríguez-Zorro et al, 2018). However, a pollen study in western Amazonia near the 105-AM site by Roucoux et al (2013) found high fern spore abundances during the formation of a peat deposit in the Late Holocene.…”
Section: Fern Sporessupporting
confidence: 84%
“…These differences support our interpretations of swamps in the early to early middle Miocene and a more dynamic fluvial system in the middle to late Miocene part of the 105-AM record. Scanty Mauritia and high Poaceae pollen were common features in surface river sediments (Gomes et al, 2021;Akabane et al, 2020) and Holocene records from fluvial lakes in Amazonia (Absy, 1979;Irion et al, 2006;Sá et al, 2016). Furthermore, high Poaceae counts in these settings can be an indicative of várezas (Akabane et al, 2020); in the 105-AM samples, Poaceae abundance correlated reasonably with abundance of floodable elements (r 2 = 0.31, P < 0.001).…”
Section: Miocene Versus Holocene Comparisonsmentioning
confidence: 75%
“…Based on this analysis we conclude that R. guianensis associated taxa (NLR: Alchornea, Araliaceae, Fabaceae, Malpighiaceae, Polygonaceae, and Sagittaria) are typical in floodplain forests such as described in modern fluvial settings in the Amazon region (Wittmann et al, 2010;Sá et al, 2016;Salamanca et al, 2016). We also observe that they rarely co-occur with taxa from Mauritiidites or Grimsdalea palm swamps, nor with taxa from the mangrove vegetation formed by Zonocostites-type pollen.…”
Section: Rhoipites Guianensis and Malvacipolloides Maristellae In Amazonian Paleoenvironmentsmentioning
confidence: 66%
“…Very high (50 -90%) amounts of Poaceae pollen in palynological records give strong evidence for the existence of savanna habitats (Salgado-Labouriau 1979, Bush 2002. However, aquatic environments can also feature large amounts of grass pollen (e.g., Behling et al 2001, Sá et al 2016. And to complicate matters further, savannas and aquatic environments are both characterized by different species of the subfamily of the Panicoideae.…”
Section: The Fossil Record and The Environmental Preference Of Grassesmentioning
confidence: 99%